Wind hazard risk assessment due to topographical condition - Mohd Fariq, Ahmad Jamil (2014)
The number of wind related disasters in Malaysia has increased suddenly. The further understanding related to wind characteristic in Malaysia are very significant in order to improve the quality of building to resist wind load. Previous study has shown that the topographical location give a significant impact to wind speed. Wind speed variations caused by small scale topography and roughness changes. This study was carried out to determine the relationship between geographical condition, its effect on the wind speed and damage ratio. By using Geographical Information System (GIS) software, 38 cases of wind related disasters in peninsular Malaysia from 2010 to 2013 were identified and analyzed. From the result, it sums up that topography are favourly significant to the wind speed and damage ratio. Then it can be conclude that the topography effect wind speed and affecting the damage ratio.